The Spawns of Creative Behavior in Team Sports: A Creativity Developmental Framework - Santos, Sara D. L.; Memmert, Daniel; Sampaio, Jaime; Leite, Nuno (Frontiers in Psychology, 2016)
Developing creativity in team sports players is becoming an increasing focus in sports sciences. The Creativity Developmental Framework is presented to provide an updated science based background. This Framework describes five incremental creative stages (beginner, explorer, illuminati, creator and rise) and combines them into multidisciplinary approaches embodied in creative assumptions. In the first training stages, the emphasis is placed on the enrollment in diversification, deliberate play and physical literacy approaches grounded in nonlinear pedagogies. These approaches allow more freedom to discover different movement patterns increasing the likelihood of emerging novel, adaptive and functional solutions. In the later stages, the progressive specialization in sports and the differential learning commitment are extremely important to push the limits of the creative progress at higher levels of performance by increasing the range of skills configurations. Notwithstanding, during all developmental stages the teaching games for understanding, a game-centred approach, linked with the constraints-led approach play an important role to boost the tactical creative behaviour. Both perspectives might encourage players to explore all actions possibilities (improving divergent thinking) and prevents the standardization in their actions. Overall, considering the aforementioned practice conditions the Creativity Developmental Framework scrutinizes the main directions that lead to a long-term improvement of the creative behaviour in team sports. Nevertheless, this framework should be seen as a work in progress to be later used as the paramount reference in creativity training.